Educación tributaria y formación ciudadana en niños de cinco años de la Institución Educativa Inicial C.J N° 160 Mi Primer Aprendizaje, Caballococha 2021 - Rios Pinedo, Judith Milagros (2022)
Relate tax education and citizenship education in five-year-old children at the initial level in the Initial Educational Institution C.J Nº160 My first apprenticeship in the city of Caballo Cocha in 2021, was the main objective of this research. As a research methodology, the type of relational research was applied, with a non-experimental, field, bivariate and cross-sectional design. The study population consisted of 87 children from the educational institution who were also part of the sample because all of them were considered. To obtain the data, the observation technique and two observation guides were used, which were validated by expert judgment. It is concluded that there is a direct and moderate association between citizenship education and tax education and that most five-year-old children 67.8% show regular citizenship education and tax education, low citizenship education and tax education in 14.9%. and good citizen training and tax education in 17.2%.